Attitudes of local people towards Apuseni Nature Park, Romania - Imecs, Zoltán; Máthé, András; Kohán, Balázs (Hungarian Geographical Bulletin, 2022)
Nature parks are protected natural areas whose purposes are the protection and conservation of landscapes in which the interaction of human activities with nature over time has created a distinct area, with significant landscape and/or cultural value, often with great biological diversity. This is the case of Apuseni Nature Park, which includes a significant karst terrain and is a very important tourist destination. In this article, we examine the attitude of local people towards the protected area with the help of a questionnaire composed of 32 questions. After the general questions, the economic situation was examined first. Then the respondents had to evaluate the values and the difficulties of their region and their relation to tourism. The answers reveal that they are aware of the importance of tourism, which may represent a serious complementary income for them. The most intriguing questions were some open-ended questions, which focused on the relationship of locals to Apuseni Nature Park. Based on the answers, we can conclude that the negative opinions slightly dominate. The dissatisfaction of the locals, the feeling of limitations due to the park are expressed in many different ways. But probably the most relevant problems can be linked to the rules and laws. As it is a nature park, people in fact, live inside the park, thus, the equilibrium between their lives and the purposes of the park should be approached. The administration of the nature park should involve local people more closely in decision-making, and maybe certain rules should be changed.